2004
DOI: 10.1002/anie.200460645
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic Figure‐Eight Octaphyrins Split into Four‐Pyrrolic Macrocycles

Abstract: Molecular mitosis: Figure‐eight octaphyrins form binuclear metal complexes that can split into two covalently spiro‐linked corrolates. In a unique case binuclear CuII [36]octaphyrin divides thermally into two CuII [18]porphyrins presumably with participation of a transient spirocyclobutane species (see schematic representation).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…85,86 Beside these, the meso-aryl expanded porphyrins are quite interesting from the viewpoint of mutual chemical interconversions (metamorphosis). 87,88 The most remarkable example is the efficient and quantitative splitting reaction of bis-Cu(II) complex of a [36]octaphyrin into two molecules of Cu(II) porphyrins upon heating. 89 This transformation requires the rapture and formation of two carboncarbon double bonds in a metathesis manner.…”
mentioning
confidence: 99%
“…85,86 Beside these, the meso-aryl expanded porphyrins are quite interesting from the viewpoint of mutual chemical interconversions (metamorphosis). 87,88 The most remarkable example is the efficient and quantitative splitting reaction of bis-Cu(II) complex of a [36]octaphyrin into two molecules of Cu(II) porphyrins upon heating. 89 This transformation requires the rapture and formation of two carboncarbon double bonds in a metathesis manner.…”
mentioning
confidence: 99%
“…[6] In addition, skeletal rearrangements and the resulting intriguing chemical reactivities, which are often triggered upon metalation have been studied. [7] In 2003, Vogel et al found that metalation of 5,24-dioxo-octaphyrin(1.1.1.0.1.1.1.0) with nickel(II) caused a rearrangement to give a bis-nickel(II) complex of spirodicorrole through the extrusion of two carbon dioxide molecules. [8] They also disclosed that the metalation of [34]octaphyrin(1.1.1.0.1.1.1.0) with palladium(II) caused a rearrangement to a bis-spirodiporphyrin skeleton.…”
mentioning
confidence: 99%
“…Octaphyrin (1.1.1.1.1.1.0.0) ( OP ), being a conjugated π system may be the excellent candidate for the materials science. Many research groups have reported the synthesis and structural properties of isomers of Octaphyrin (1.1.1.1.1.1.0.0) (Franck and Nonn, 1995; Latos-Grazynski, 2004; Shimizu et al, 2005; Rath et al, 2005b; Geffroy et al, 2006; Hiroto et al, 2006; Kumar et al, 2007; Misra and Chandrashekar, 2008; Anaka et al, 2011; Sasabe and Kido, 2011, 2013a,b; Mori et al, 2012a; Jin and Tang, 2013; Kido et al, 2013; Naoda and Osuka, 2014; Sekine et al, 2014; Islam and Pandith, 2014a; Anguera et al, 2015; Romain et al, 2015). According to Chandershaker et al the core-modified expanded porphyrins containing 26, 36, and 54 π electrons because of their exceptionally massive two-photon absorption cross- sections may be considered among the most effective appropriate candidates, particularly as organic NLO materials (Pushpan and Chandrashekar, 2002).…”
Section: Introductionmentioning
confidence: 99%